Digital Entrepreneurship Intention in University Students: Systematic Literature Review and Research Agenda - Indira, Fransisca Rahcmawati; Wardani, Dewi Kusuma; Murwaningsih, Tri (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2024)
The advent of digital technology, particularly the internet, has revolutionized the traditional entrepreneurial process into digital entrepreneurship. The objectives of this study are twofold: (1) to identify the key factors that form digital entrepreneurship intentions among college students, and (2) to outline potential themes for future research. The research method used is Systematic Literature Review (SLR) to examines various types of research conducted between 2017 and 2023. Based on results data collection 209 publication articles were obtained from the Scopus database, through the validation and extraction process obtained 29 research articles relevant to the issue and criterion to reviewed. The research results reveal five key factors shaping the digital entrepreneurship intentions in university students. These factors comprise cognitive, individual, educational, environmental, and demographic factors. Remarkably, the study highlights the dominance of individual factors, cognitive factors, and Theory of Planned Behaviour models within the realm of digital entrepreneurship study. Furthermore, future research is suggested to explore environmental and demographic factors. Given the essential opportunities, it is imperative to carry out further study to probe into the digital entrepreneurship intentions of university students.